Wage System Reform during the Mangkunegara IV Period: Analysis of the Manuscript Paring Dalêm Pananggalan (Balandja) dhatêng Putra Santana tuwin Abdi 1871-1872. - Arsyta Wulandari; Sisyono Eko Widodo (Pusat Unggulan Ipteks Javanologi Universitas Sebelas Maret, 2024)
This research aims to determine the content contained in the PDP text related to the provision of salaries in the form of money to the servants and putra santana Dalêm after the withdrawal of the appanage system. That matter is based on the PDP manuscript, which has been edited to produce text that is free from errors. The PDP manuscript is an archival manuscript from the Mangkunegaran Reksapustaka Library collection. After carrying out analysis using philological work steps, 29 errors were found in the PDP manuscript. The PDP manuscript contains the salaries and allowances given by the king to courtiers and relatives of the king after the withdrawal of the appanage. The salaries given to courtiers are detailed in each kawedanan, along with their position. Based on their location or existence, kawedanan is divided into two. However, based on their duties there are 9 kawedanan, this is in accordance with the pranatan that was issued by Mangkunegara IV on 11 August 1867. The allowances given by the king to his relatives are also detailed per family. Apart from wages and allowances, there is also the amount of land tax that must be paid by the king's relatives. The currency used at that time was rupiyah pethak and sen.